Mechanical Analysis and Measurements of a Multicomponent NbTi/Cu Superconducting Magnets Structure for the Fully Superconducting Electron Cyclotron Resonance Ion Source*Supported by the National Natural Science Foundation of China under Grant No 11302225, and the China Postdoctoral Science Foundation under Grant Nos 2014M560820 and 2015T81071. (May 2016) - Guan 关, Ming-Zhi 明智; Hu 胡, Qiang 强; Gao 高, Pei-Feng 配峰; Wang 王, Xing-Zhe 省哲; Yang 杨, Tong-Jun 通军; Wu 吴, Wei 巍; Xin 辛, Can-Jie 灿杰; Wu 吴, Bei-Min 北民; Ma 马, Li-Zhen 力祯
Abstract : A fully superconducting electron cyclotron resonance (ECR) ion source (SECRAL II) is currently being built in the Institute of Modern Physics, Chinese Academy of Sciences. Its key components are three superconducting solenoids (Nb-Ti/Cu) and six superconducting sextupoles (Nb-Ti/Cu). Different from the conventional superconducting ECR magnetic structure, the SECRAL II includes three superconducting solenoid coils that are located inside the superconducting sextupoles. The SECRAL II can significantly reduce the interaction forces between the sextupole and the solenoids, and the magnets can also be more compact in size. For this multi-component SECRAL II generating its self field of ~8 T and being often exposed to the high self field, the mechanical analysis has become the main issue to keep their stress at < 200 MPa on coils. The analytical and experimental results in mechanics are presented in the SECRAL II structure. To improve the accuracy and efficiency of analysis, according to the composite rule of micromechanics, the equivalent uniform windings are used to simulate the epoxy-impregnated Nb-Ti/Cu coils. In addition, using low temperature strain gauges and a wireless fast strain acquisition system, a fundamental experiment on the strains developments of a sextupole is reported. Finally, based on our analysis, the stresses and deformations for its assembly of each SECRAL II coil will be further optimized.